Hubungan antara Tingkat Kecemasan dan Perubahan Tekanan Darah pada Pasien Pencabutan Gigi - Mintjelungan, Christy N.; Rompas, Irene F.; Tato, Enjelin M. (Universitas Sam Ratulangi, 2025)
Abstract: In dental practice, emotional states, stress, and anxiety are often found in patients. This situation can trigger a defense reaction characterized by increased sympathetic nerve activity. Blood pressure can be used as a parameter to detect the increase in sympathetic nerve activity resulting in changes in blood pressure before the tooth extraction procedure. This study aimed to evaluate the relationship between anxiety levels and changes in blood pressure in tooth extraction patients at Public Health Center. This was a descriptive and analytical study with a cross-sectional approach. Samples were taken using purposive sampling method. The results obtained 50 patients at Puskesmas Sario (Public Health Center) as respondents There were 11 respondents who were not anxious: nine (18%) respondents with fixed blood pressure, one (2%) respondent with lower blood pressure, and one (2%) respondent with increased blood pressure. There were 39 respondents with “anxiety” levels of anxiety including nine (18%) respondents with fixed blood pressure, seven (14%) with decreased blood pressure, and 23 (46%) with increased blood pressure. The paired t-test obtained a p-value of 0.001 for the relationship between anxiety level and blood pressure before tooth extraction. In conclusion, there is a relationship between the level of anxiety and changes in blood pressure in patients before the tooth extraction procedure is carried out. Keywords: anxiety; blood pressure; tooth extraction. Abstrak: Dalam praktik kedokteran gigi, keadaan emosi, stres, dan kecemasan sering dijumpai pada pasien yang berkunjung ke dokter gigi. Keadaan ini dapat memicu reaksi pertahanan yang ditandai dengan peningkatan aktivitas saraf simpatis. Tekanan darah dapat digunakan sebagai parameter untuk mendeteksi adanya peningkatan aktivitas saraf simpatis, yang dapat menghasilkan perubahan tekanan darah sebelum dilakukan prosedur pencabutan gigi. Penelitian ini bertujuan untuk mengevaluasi hubungan antara tingkat kecemasan dan perubahan tekanan darah pada pasien pencabutan gigi di Puskesmas. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang. Sampel penelitian diperoleh menggunakan metode purposive sampling. Hasil penelitian mendapatkan 50 pasien di Puskesmas Sario sebagai responden. Terdapat 11 responden yang tidak cemas dan di antaranya terdapat sembilan (18%) responden yang tekanan darahnya bernilai tetap, satu (2%) responden dengan tekanan darah turun, dan satu (2%) responden dengan tekanan darah meningkat. Terdapat 39 responden dengan tingkat kecemasan “cemas” di antaranya sembilan (18%) responden tekanan darahnya tetap, tujuh (14%) responden tekanan darah turun, dan 23 (46%) responden dengan tekanan darah meningkat. Hasil uji t berpasangan terhadap hubungan antara tingkat kecemasan dan perubahan tekanan darah sebelum pencabutan gigi mendapatkan nilai p=0,001 (<0,005). Simpulan penelitian ini ialah terdapat hubungan antara tingkat kecemasan dengan perubahan tekanan darah pada pasien sebelum dilakukan tindakan pencabutan gigi. Kata kunci: tingkat kecemasan; perubahan tekanan darah; pencabutan gigi